2019
DOI: 10.1007/s00520-019-04920-z
|View full text |Cite
|
Sign up to set email alerts
|

Deglutition disorders as a consequence of head and neck cancer therapies: a systematic review and meta-analysis

Abstract: Purpose In this study, we aimed to estimate the frequency of deglutition disorders in patients pre-and post-treatment for head and neck cancer (HNC). Methods Search strategies were developed for the following databases: LILACS, PubMed, SpeechBITE, LIVIVO, Web of Science, and Scopus. Additionally, the gray literature was searched using Google Scholar, OpenGrey, and ProQuest. Only studies that conducted an evaluation of deglutition before and after cancer treatment and had sufficient quantitative data were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 38 publications
4
19
0
1
Order By: Relevance
“…The aim of this study was to investigate if easily attainable clinical markers could be considered predictors for severe dysphagia, among patient data, tumor and treatment characteristics. 35% of the cohort in the present study had a PAS ≥5, which corresponds well to other studies reporting prevalence around 35% for aspiration and/or penetration among HNC patients 44,45 . According to the results increasing BMI and patients with tumor of the tonsil and overweight were less likely suffer from severe dysphagia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The aim of this study was to investigate if easily attainable clinical markers could be considered predictors for severe dysphagia, among patient data, tumor and treatment characteristics. 35% of the cohort in the present study had a PAS ≥5, which corresponds well to other studies reporting prevalence around 35% for aspiration and/or penetration among HNC patients 44,45 . According to the results increasing BMI and patients with tumor of the tonsil and overweight were less likely suffer from severe dysphagia.…”
Section: Discussionsupporting
confidence: 90%
“…35% of the cohort in the present study had a PAS ≥5, which corresponds well to other studies reporting prevalence around 35% for aspiration and/or penetration among HNC patients. 44 , 45 According to the results increasing BMI and patients with tumor of the tonsil and overweight were less likely suffer from severe dysphagia. Weight‐loss following treatment of 7.5% or more and use of feeding tube at time of VFS were predictors of severe dysphagia, with increasing risk with each month's use of a feeding tube.…”
Section: Discussionmentioning
confidence: 97%
“…Two patients suffered from aspiration and three other patients were diagnosed with penetration (PAS). In a previous meta-analysis of deglutition disorders extracted from 17 studies including 229 patients, Porto de Toledo et al reported a high frequency of aspiration in 28.6% of patients immediately posttreatment and during the following three months [ 28 ]. For the course of six months posttreatment, this meta-analysis revealed a penetration of fluids above the vocal folds and an impairment of laryngeal elevation.…”
Section: Discussionmentioning
confidence: 99%
“…From the studies analyzed within the meta-analysis [ 28 ], only the trial of Patterson et al [ 29 ] used FEES as we did. They observed in 8 of 97 patients a silent aspiration at three months posttreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Research reports that up to 90% of patients with HNC have eating and drinking difficulties after treatment [11,12]. A potential range of side effects can inhibit a patient's ability to eat and drink, including pain, xerostomia, mucositis, nausea, lack of appetite, dysphagia, and dysgeusia [11,13].…”
Section: Introductionmentioning
confidence: 99%